Trade policy changes, tax evasion and Benford’s law - Demir, B; Javorcik, B (Elsevier, 2020)
This paper draws attention to import duty evasion as a margin through which firms adjust to changes in trade policy. This margin is different from the other forms of adjustment, as it can be employed very fast and thus it may constitute the initial reaction to the shock before a slower adjustment through the other channels takes place. The study also proposes a new method of detecting tax evasion in international trade, based on deviations from Benford's law. It applies the method in the context of an unexpected policy change in Turkey that increased the cost of import financing. The results are consistent with an immediate increase in tax evasion in the affected import flows, which dies down a year later. A standard approach to detecting tariff evasion, based on “missing trade”, confirms these conclusions.